Drilled to Write : Becoming a Cadet Writer at a Senior Military College - Rifenburg, J. Michael, 1982- (Book collections on Project MUSE., 2022)
"Drilled to Write offers an account of U. S. Army cadets navigating Army writing at a senior military college. Through a case study, Rifenburg follows a cadet, Logan Blackwell, and traces how he conceptualizes Army writing through military science classes, tactical exercises in the Appalachian Mountains, and specialized schools"--